Forest foods and healthy diets: quantifying the contributions - Rowland, D.; Ickowitz, A.; Powell, B.; Nasi, Robert; Sunderland, Terry C.H. (Cambridge University Press, 2017)
Forested landscapes provide a source of micronutrient rich food for millions of people around the world. A growing evidence base suggests these foods may be of great importance to the dietary quality of people living in close proximity to forests – especially in communities with poor access to markets. Despite widespread evidence of the consumption of forest foods around the world, to date, few studies have attempted to quantify the nutritional contributions these foods make. In this study we tested the hypothesis that the consumption of forest foods can make important contributions to dietary quality. We investigated the dietary contributions of wild forest foods in smallholder dominated forested landscapes from 37 sites in 24 tropical countries, using data from the Poverty and Environment Network (PEN). We compared quantities of forest foods consumed by households with dietary recommendations and national average consumption patterns. In addition, we compared the relative importance of forests and smallholder agriculture in supplying fruits, vegetables, meat and fish for household consumption. More than half of the households in our sample collected forest foods for their own consumption, though consumption patterns were skewed towards low-quantity users. For high-quantity consuming households, however, forest foods made a substantial contributions to their diets. The top quartile of forest food users in each site obtained 14.8% of the recommended amounts of fruits and vegetables, and 106% of the reference quantity of meat and fish from forests. In 13 sites, the proportion of meat and fish coming from forests was greater than from domestic livestock and aquaculture, while in 11 sites, households procured a greater proportion of fruits and vegetables from forests than from agriculture. Given high levels of heterogeneity in forest food consumption, we identify four forest food use site typologies to characterize the different use patterns: ‘forest food dependent’, ‘limited forest food use’, ‘forest food supplementation’ and ‘specialist forest food consumer’ sites. Our results suggest that while forest foods do not universally contribute significantly to diets, in some sites where large quantities of forest foods are consumed, their contribution towards dietary adequacy is substantial.